UPAYA MENINGKATKAN HASIL BELAJAR PKN MATERI MENGHARGAI KEPUTUSAN BERSAMA MELALUI METODE DISKUSI TIPE BUZZ GROUP KELAS VD SD NEGERI 01 LIMO KAUM - Helni Paita (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Pkn subjects are subjects that include material that leads to the formation of personality values of students, Based on research experience in the field of student learning outcomes in Citizenship Education subjects are relatively low compared to other subjects, such as in social studies subjects, researchers Seeing the involvement and understanding of students in understanding the material shows that students respond well, because the media needed related to the material is on the walls of the class but is still limited. The method used in this study is the buzz group type discussion method. In the learning process the buzz group type discussion method is carried out in the middle of learning. The discussion method of buzz group type is carried out with discussion rules that have been made, group formation and design according to the formation that has been used, guiding the course of discussion, completing discussion topics in accordance with the material already discussed, reading the results of the discussion represented by the group leader, concluding the discussion results and students with teacher guidance conclude the material that has been studied as a whole. Based on the learning outcomes of VD class students in the first cycle obtained an average score of 69 which was completed as many as 11 students or 55% while in the second cycle there was an increase with an average value of 83.5 and students who completed as many as 17 students or 85%. From the description above, it can be concluded, that the learning outcomes of Civics Class VD at SD Negeri 01 Limo Kaum using the buzz group type of discussion method increased.